Advantages and Barriers to Adoption of Green BIM in the Construction Industry of Sindh - Razak, Abdur Razzaque; Memon, Nafees Ahmed (Tropical Scientific Journal, 2023)
Objective: Green BIM, has gained the attention of researchers in last decade all over the world. Many construction industries are presently adopting Green BIM to improve construction practices and provide long-term advantages. Despite the long term benefits of this new technology, Green BIM technology in the construction industry still lacking in many countries, especially in Pakistan construction industry. Therefore, this research aims to enhance BIM enabled the sustainable design and explores its advantages and barriers in adopting the green BIM. Research Method: This research was carried out quantitatively where data collection was carried out through a questionnaire survey to identify the advantages of green BIM and barriers in adopting of green BIM in construction industry of Sindh. A total 75 questionnaire forms were collected from clients, consultants, employees and contractors. Findings: 58% factors were identified as advantages of green BIM and the 66% were identified as top barriers come in the adoption of green BIM. Originality: This study will help professionals to understand the advantages of green BIM and also its barriers and their mitigation measures in the construction industry